The European Regulatory Framework of Ranking Transparency on Platform Markets – P2B + P2C = P2U - Katja Nolteernsting (IIC - International Review of Intellectual Property and Competition Law, 2025)
Since 2020 at the latest, transparency requirements for the ranking on online platforms have existed in the EU. The European legislature has introduced parallel, but also interacting, "similar" requirements for online platforms relating, on the one hand, to commercial platform users and, on the other hand, to consumers. However, this seemingly obvious approach brings about redundancies and an unclear scope of the information requirements, as the present, according to the European Commission insufficient, information level on platforms shows. This article will explore how much transparency is really required. It aims to show that, though somewhat counterintuitively, transparency requirements in relationships with commercial users ("P2B") and consumers ("P2C") are not only similar, but are to be treated identically. Consequently, the present regulatory framework is in need of reform with regard to both the wording of the provisions and their regulatory structure. The article will first outline the principles of a platform economy (Sect. 1 ) and the legal situation before 2019 (Sect. 2 ). Then it will critically analyse the matrix structure of the current regulatory system (Sects. 3 and 4 ). The focus will be placed on concretising the transparency requirements as laid down by the P2B Regulation, on the one hand, and the UCP Directive, on the other. In this regard, the main questions are: Which level of detail of information is required and does the required level of detail differ in P2B and P2C relationships? The relationship with other provisions will also be discussed (Sect. 5 ). Finally, the article will summarise the findings and provide a proposal for a coherent regulatory framework with a clear wording mirroring the key objective of the regulatory project (Sect. 6 ).
Keywords: 340; Platform economy; UCP Directive; Transparency requirement